Conceptual energy and water recovery system for self-sustained nano membrane toilet. (15th October 2016) - Hanak, Dawid P.; Kolios, Athanasios J.; Onabanjo, Tosin; Wagland, Stuart T.; Patchigolla, Kumar; Fidalgo, Beatriz; Manovic, Vasilije; McAdam, Ewan; Parker, Alison; Williams, Leon; Tyrrel, Sean; Cartmell, Elise
Highlights: Energy and water recovery system from human excreta is modelled in Aspen Plus. The Nano Membrane Toilet is proven to be a self-sustained system. Up to 87% of total amount of water fed to the system can be recovered. Net power output of the entire system is similar to the USB port peak power (2–6 W). The specific net power output varies between 23.1 and 69.2 Wh/kgsettledsolids . Abstract: With about 2.4 billion people worldwide without access to improved sanitation facilities, there is a strong incentive for development of novel sanitation systems to improve the quality of life and reduce mortality. The Nano Membrane Toilet is expected to provide a unique household-scale system that would produce electricity and recover water from human excrement and urine. This study was undertaken to evaluate the performance of the conceptual energy and water recovery system for the Nano Membrane Toilet designed for a household of ten people and to assess its self-sustainability. A process model of the entire system, including the thermochemical conversion island, a Stirling engine and a water recovery system was developed in Aspen Plus®. The energy and water recovery system for the Nano Membrane Toilet was characterised with the specific net power output of 23.1 Wh/kgsettledsolids and water recovery rate of 13.4 dm 3 /day in the nominal operating mode. Additionally, if no supernatant was processed, the specific net power output was increased to 69.2 Wh/kgsettledsolids . Such household-scale system would deliver the net power output (1.9–5.8 W). This was found to be enough to charge mobile phones or power clock radios, or provide light for the household using low-voltage LED bulbs.